2020
DOI: 10.4047/jap.2020.12.3.107
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the improperly scanned scan body images on the accuracy of virtual implant positioning in computer-aided design software

Abstract: PURPOSE.The aim of this study was to examine the importance of the defect-free scanning of a scan body by assessing the accuracy of virtual implant positioning in computer-aided design (CAD) software when the scan body image is improperly scanned. MATERIALS AND METHODS. A scan body was digitized in a dentiform model using an intraoral scanner, and scanned images with differing levels of image deficiency were generated: 5%, 10%, and 15% deficiency in the flat or rounded area. Using a best-fit image matching alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 32 publications
2
17
0
Order By: Relevance
“…However, the present study confirmed that a meticulous full scan of the entire areas of the ISBs is important even when scanning an implant case using ISBs. This is consistent with the finding of Park et al that the imaging deficiency of the ISB influenced the position of the virtual implant; these authors suggested that a surface area deficiency of more than 10% in an ISB should be avoided [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the present study confirmed that a meticulous full scan of the entire areas of the ISBs is important even when scanning an implant case using ISBs. This is consistent with the finding of Park et al that the imaging deficiency of the ISB influenced the position of the virtual implant; these authors suggested that a surface area deficiency of more than 10% in an ISB should be avoided [24].…”
Section: Discussionsupporting
confidence: 92%
“…Most previous studies have investigated either complete or partial but multiple edentulous cases, and there have been very few studies on the accuracy of implant digital impressions according to the ISB orientation or scanning method in cases of single implants. One previous study found that the deficiency of the scanned image of the ISB affects the position of the virtual implant in the single implant case, but that study only considered a single oral scanner, and it simulated deficient scan images experimentally after completing the scanning procedure [24].…”
Section: Introductionmentioning
confidence: 99%
“…Effective shape and size of markers should be investigated to reduce the faulty processing of digitization in further studies. In addition, the scan strategy, image reconstruction software, operator experience are another major factors influencing the quality of a scan [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The opposite is correct as well, in that, absent data points in a point cloud will lead to difficulties when the surface geometry is reconstructed, which might cause multiple errors when attempting to register the image and associate the ISB surface with the implant library which means true image matching is impossible. 1,6 IOS systems are known to be open, closed, and semi-closed architectures, which is an indication of the degree of flexibility in importing and exporting digital files. Many authors have recommended open or semi-closed systems as they offer the laboratory and clinician more freedom and flexibility.…”
Section: Introductionmentioning
confidence: 99%